2020
DOI: 10.3390/microorganisms8122040
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Gut Microbiome Differences between Ferric Citrate and Calcium Carbonate Phosphate Binders in Patients with End-Stage Kidney Disease

Abstract: Gut dysbiosis in patients with chronic kidney disease (CKD) may induce chronic inflammation and increase morbidity. Phosphate-binding agents, generally used in patients with CKD, may potentially change the composition of the gut microbiota. This study aimed to compare the microbiota composition in hemodialysis patients treated with ferric citrate or calcium carbonate. The stool microbiota was investigated in hemodialysis patients treated with ferric citrate (n = 8) and calcium carbonate (n = 46) using 16S rRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…Consistent with the alleviated DKD symptoms in Db-FM groups, improvement in the gut microbiota was also identified. In line with what we found, the reduction of bacterial diversity has been reported previously exist in patients ( 63 , 64 ) and animal models ( 65 ) with kidney disease. We, therefore, speculate that the promotion of microbial diversity index may be attributed to the prebiotic properties of FG-FM and beneficial for the alleviation of nephropathy symptoms in diabetic mice ( 66 ).…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the alleviated DKD symptoms in Db-FM groups, improvement in the gut microbiota was also identified. In line with what we found, the reduction of bacterial diversity has been reported previously exist in patients ( 63 , 64 ) and animal models ( 65 ) with kidney disease. We, therefore, speculate that the promotion of microbial diversity index may be attributed to the prebiotic properties of FG-FM and beneficial for the alleviation of nephropathy symptoms in diabetic mice ( 66 ).…”
Section: Discussionsupporting
confidence: 93%
“…On top of these untoward effects of dietary intervention on vitamin K intake, different PBs have been shown, both in vitro and in vivo, to bind vitamin K, thereby limiting its bioavailability [15][16][17]. Sevelamer seems to bind vitamin K directly [16]; however, there might also be an effect on microbiota by sevelamer and calcium carbonate treatment [35,36]. Moreover, in patients on renal replacement therapy, an association of sevelamer carbonate use and increased dp-ucMGP levels was observed, suggesting that PB therapy aggravates vitamin K deficiency [18].…”
Section: Discussionmentioning
confidence: 99%
“…They observed that CKD rats had lower relative abundances of some Firmicutes and Lactobacillus and a lower gut microbial diversity compared to normal rats, but they also described that ferric citrate treatment in CKD rats increased bacterial diversity almost to levels observed in control rats and that this treatment did not increase uremic toxins. In a recent study, Wu et al [36], compared hemodialysis patients gut microbiome treated with either calcium carbonate or ferric citrate. They observed a significantly increased microbial diversity in the group treated with ferric citrate, with an increased abundance of Bacteroidetes and a decreased abundance of Firmicutes.…”
Section: Discussionmentioning
confidence: 99%